Burnout Disrupts Anxiety Buffer Functioning Among Nurses: A Three-Way Interaction Model - Trifiletti, Elena; Pedrazza, Monica; Berlanda, Sabrina; Pyszczynski, Tom (Frontiers in Psychology, 2017)
Over the last 40 years, job burnout has attracted a great deal of attention among researchers and practitioners and, after decades of research and interventions, it is still regarded as an important issue . With the aim of extending the Anxiety Buffer Disruption Theory (ABDT), in this paper we argue that high levels of burnout may disrupt the anxiety buffer functioning that protects people from death concerns. ABDT was developed from Terror Management Theory (TMT). According to TMT, reminders of one's mortality are an essential part of humans’ daily experience and have the potential to awake paralyzing fear and anxiety. In order to cope with death concerns, people typically activate an anxiety-buffering system centered on their cultural worldview and self-esteem. Recent ABDT research shows that individuals with Posttraumatic Stress Disorder (PTSD) are unable to activate such anxiety buffering defenses . In line with these results, we hypothesized that the burnout syndrome may have similar effects, and that individuals with higher levels of burnout will be less likely to activate an anxiety buffering response when their mortality is made salient. Participants were 418 nurses, who completed a questionnaire including: a mortality salience (MS) manipulation, a delay manipulation, and measures of burnout, work-related self-efficacy, and representation of oneself as a valuable caregiver. Nurses are daily exposed both to the risk of burnout and to mortality reminders, and thus constituted an ideal population for this study. In line with an anxiety buffer disruption hypothesis, we found a significant three-way interaction between burnout, mortality salience and delay. Participants with lower levels of burnout reported higher levels of self-efficacy and a more positive representation as caregivers in the MS condition compared to the control condition, when there was a delay between MS manipulation and the assessment of the dependent measures. The difference was non-significant for participants with higher levels of burnout. Theoretical and practical implications of findings are discussed.